An experimental study on the effect of injection pressure on diesel PCCI engine. Issue 1 (31st December 2022) - Sathishkumar, S.; Mohamed Ibrahim, M.
Abstract : The aim of this work was to analyse the effects of injection pressure and exhaust gas recirculation (EGR) on combustion, performance and emissions characteristics of diesel premixed charge compression ignition (PCCI) mode. In this work, the injection pressure of diesel varied from 500 to 1000 bar. The optimum injection pressure in diesel PCCI mode was identified based on the engine performance and emissions. The thermal efficiency was improved and smoke emission was drastically reduced as increasing injection pressure. However, injection pressure did not significantly influence the amount of NO, HC and CO emissions. The diesel PCCI mode was possible until a brake mean effective pressure (BMEP) of 2 bar since there was a vigorous knocking at higher BMEPs. The addition of EGR retarded the combustion process, suppressed the knocking, increased the thermal efficiency and extended the operating range to higher BMEPs of 3 and 4 bars.